2015
DOI: 10.1016/j.virusres.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Cucumber mosaic virus isolates in western New York State during epidemic years

Abstract: In the early 2000s an epidemic of cucumber mosaic virus (CMV) spread within the Midwestern and Eastern US affecting snap and dry bean (Phaseolus vulgaris L.) cultivation. Fifty one CMV isolates from this period were partially characterized from varied hosts by sequencing a section from each of the three genomic RNAs. Aside from one subgroup II strain from pepper, all isolates, including those from snap bean, fell within the IA subgroup. The nucleotide sequence diversity of virus populations sampled at multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
8
0
3
Order By: Relevance
“…Those for the three genomic RNAs in S11 were MH567347, MH567348, and MH567349, and those for S12 were MH567350, MH567351, and MH567354. These sizes are consistent with those reported elsewhere (Thompson et al, 2015).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Those for the three genomic RNAs in S11 were MH567347, MH567348, and MH567349, and those for S12 were MH567350, MH567351, and MH567354. These sizes are consistent with those reported elsewhere (Thompson et al, 2015).…”
Section: Resultssupporting
confidence: 94%
“…CMV can be subdivided into two main phylogenetic Subgroups I and II, sharing 70–75% nucleotide sequence identity making them taxonomically separate species. Subgroup I can be further subdivided into IA and IB, with IB being predominantly Asian in distribution (Palukaitis and García-Arenal, 2003; Jacquemond, 2012; Kim et al, 2014; Thompson et al, 2015). BLAST search and neighbor-joining phylogenetic analysis showed that the genomic sequences of RNAs 1, 2 of the CMV isolated in central Kenya most closely associate with corresponding CMV RNA segments of South Korean origin, sharing up to 94 and 92% nucleotide sequence identity respectively, that belong to CMV Subgroup IA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we use selective 2′-hydroxyl acylation analyzed by primer extension sequencing (SHAPE-Seq) v2.1 ( 40 ) and covariation analysis to analyze the complete sequence of RNA3 from CMV strain Bn57 ( 41 ). Using SHAPE-Seq, we directly compare nucleotide flexibility across RNA3 in infected cell lysates and in vitro refolded purified viral RNA and present predicted secondary structure maps of RNA3 using SHAPE-Seq data to restrain secondary structure predictions.…”
Section: Introductionmentioning
confidence: 99%
“…CMV, the most frequently occurring virus in peppers, belongs to the genus Cucumovirus in the plant virus family Bromoviridae, and it infects over 1000 plant species in 85 families (El-Borollosy and Oraby, 2012). Since it was discovered as the causal disease agent of cucurbit hosts in 1916 (Doolittle, 1916;Jagger, 1916), CMV has been reported to infect cucumber, melon, zucchini, soybean, and tobacco (Baskaran et al, 2016;Mochizuki et al, 2014;Roossinck et al, 1990;Thompson et al, 2015). In Korea, the virus is associated with over 33% of chili pepper infections, and causes losses valued at approximately $200 million dollars each year.…”
Section: Introductionmentioning
confidence: 99%